أساليب ترجمة النصوص الإعلانية من الإنجليزية إلى العربية = Translation methods of advertisements from English into Malay = Terjemahan iklan daripada Bahasa Inggeris ke Bahasa Melayu - Haji Ibrahim, Majdi; Jakfar Nasruddin, Rozana (Kulliyyah of Islamic Revealed and Human Sciences (KIRKHS), International Islamic University Malaysia, 2019)
يهدف هذا البحث إلى تناول أهم أساليب الترجمة المستخدمة في ترجمة النصوص الإعلانية، وهي النصوص التي تهدف إلى نقل إعلان تجاري من شأنه أن ينتج تأثيرا على جمهور اللغة المستهدفة يماثل التأثير الذي تركه الإعلان الأصلي على جمهور اللغة المصدر. ولضمان نجاح ترجمة الإعلان ينبغي مراعاة جميع عناصر الإعلان أثناء عملية الترجمة، بما في ذلك المنتج المعلن عنه، وصاحب المنتج، وتصميم الإعلان، والجمهور المتلقي، بل وحتى سياسية الحكومة في بلد الإعلان، وقد يؤدي اختيار إستراتيجية خاطئة في ترجمة الإعلان إلى رفض الإعلان وكساد المنتج المعلن عنه. سيركز البحث على تناول أهم أساليب الترجمة المستخدمة في ترجمة النصوص الإعلانية وذلك من خلال تحليل نماذج من ترجمة إعلانات لمنتجات عالمية مشهورة من الإنجليزية إلى العربية، وتكشف نتائج البحث أن المترجمين في ترجمة عناوين الإعلانات يميلون إلى أسلوب التحويل بالزرع أو النقرحة، بينما يفضلون في ترجمة شعارات الإعلانات استخدام أسلوب النقل، أو التكييف، أو إعادة الكتابة ***************************************************************************************** .This paper demonstrates translation approaches used in translating advertising texts. The main purpose of translating advertising texts is to transmit the message that would produce the same impact on almost all the readers of the target language. To achieve this objective, all elements of advertisement need to be observed during the translation process such as the product, advertisers, designers, text receivers, and even the government’s policies which the translation of advertisement takes place. Choosing the wrong strategy might cause the translations to be rejected by the target culture. The focus of this research is to explain strategies of translating advertising texts from English into Arabic. The findings reveal that in translating headlines translators tend to use the strategy of borrowing, whereas in translating slogans, translators tend to use literal translation, adaptation strategy, or rewriting. ******************************************************************************************* Kajian ini bertujuan untuk menunjukkan pendekatan terjemahan yang digunakan dalam menterjemahkan teks iklan. Tujuan utama menterjemahkan teks iklan adalah untuk menyampaikan mesej yang akan memberi kesan yang sama kepada pembaca bahasa sasaran. Untuk mencapai matlamat ini, semua elemen iklan, bukan sahaja produk, pengiklan, pereka bentuk, penerima teks, bahkan dasar kerajaan dimana iklan tersebut diiklankan perlu diambil kira semasa proses terjemahan. Pemilihan strategi terjemahan iklan yang salah boleh mengakibatkan iklan tersebut ditolak. Kajian ini akan memfokuskan analisis dan perbincangan model iklan bahasa Inggeris yang diterjemahkan ke dalam bahasa Arab. Hasil carian mendedahkan bahawa penterjemah cenderung menggunakan strategi peminjaman dalam menterjemahkan tajuk utama iklan, manakala dalam menterjemahkan slogan, penterjemah cenderung menggunakan terjemahan harfiah, strategi adaptasi, atau menulis semula.